Gamma Interferon Is Critical for Neuronal Viral Clearance and Protection in a Susceptible Mouse Strain following Early Intracranial Theiler's Murine Encephalomyelitis Virus Infection - Rodriguez, Moses (American Society for Microbiology, 2003)
We evaluated the role of gamma interferon (IFN-γ) in protecting neurons from virus-induced injury following central nervous system infection. IFN-γ(−/−) and IFN-γ(+/+) mice of the resistant major histocompatibility complex (MHC) H-2(b) haplotype and intracerebrally infected with Theiler's murine encephalomyelitis virus (TMEV) cleared virus infection from anterior horn cell neurons. IFN-γ(+/+) H-2(b) mice also cleared virus from the spinal cord white matter, whereas IFN-γ(−/−) H-2(b) mice developed viral persistence in glial cells of the white matter and exhibited associated spinal cord demyelination. In contrast, infection of IFN-γ(−/−) mice of the susceptible H-2(q) haplotype resulted in frequent deaths and severe neurologic deficits within 16 days of infection compared to the results obtained for controls. Morphologic analysis demonstrated severe injury to spinal cord neurons in IFN-γ(−/−) H-2(q) mice during early infection. More virus RNA was detected in the brain and spinal cord of IFN-γ(−/−) H-2(q) mice than in those of control mice at 14 and 21 days after TMEV infection. Virus antigen was localized predominantly to anterior horn cells in infected IFN-γ(−/−) H-2(q) mice. IFN-γ deletion did not affect the humoral response directed against the virus. However, the level of expression of CD4, CD8, class I MHC, or class II MHC in the central nervous system of IFN-γ(−/−) H-2(q) mice was lower than those in IFN-γ(+/+) H-2(q) mice. Finally, in vitro analysis of virus-induced death in NSC34 cells and spinal motor neurons showed that IFN-γ exerted a neuroprotective effect in the absence of other aspects of the immune response. These data support the hypothesis that IFN-γ plays a critical role in protecting spinal cord neurons from persistent infection and death.